2001
DOI: 10.1603/0022-0493-94.2.529
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamics of Adaptation to Transgenic Corn by Western Corn Rootworm (Coleoptera: Chrysomelidae)

Abstract: A simulation model of the population dynamics and genetics of the western corn rootworm, Diabrotica virgifera virgifera LeConte, was created for a landscape of corn, soybean, and other crops. Although the model was created to study a 2-locus problem for beetles having genes for resistance to both crop rotation and transgenic corn, during this first phase of the project, the model was simulated to evaluate only resistance management plans for transgenic corn. Allele expression in the rootworm and toxin dose in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
166
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(190 citation statements)
references
References 36 publications
15
166
0
1
Order By: Relevance
“…The long-term regional suppression of pink bollworm reported here may further reduce insecticide use and enhance implementation of the refuge strategy, which is mandated by the U.S. Environmental Protection Agency for delaying evolution of pest resistance to Bt cotton (2)(3)(4)(5)(6)(7)(8). This strategy requires that growers plant refuges of non-Bt cotton to promote survival of susceptible pests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term regional suppression of pink bollworm reported here may further reduce insecticide use and enhance implementation of the refuge strategy, which is mandated by the U.S. Environmental Protection Agency for delaying evolution of pest resistance to Bt cotton (2)(3)(4)(5)(6)(7)(8). This strategy requires that growers plant refuges of non-Bt cotton to promote survival of susceptible pests.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic cultivars of cotton and maize that produce toxins from Bacillus thuringiensis (Bt) to control insect pests were grown on 12 million hectares worldwide during 2001 (1). A major concern is that rapid evolution of resistance by pests could nullify the benefits of Bt crops (2)(3)(4)(5)(6). It has also been proposed, however, that Bt crops imposing high mortality could cause regional suppression of target pests before resistance occurs (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Even if emergence is delayed in transgenic insecticidal corn, the last males emerging from refuge corn can mate with females for 30 d or more (Quiring and Timmins 1990). In a simulation study, Onstad et al (2001) concluded that, when sublethal effects of transgenic corn cause susceptible phenotypes to emerge later than normal in a block conÞguration, resistance can evolve faster when resistance is recessive. When resistance is recessive and only homozygous susceptibles are delayed 6 d, the time to 3% resistance allele frequency was shortened in situations in which the insecticidal corn was not very efÞcacious.…”
Section: Submodel For Adultsmentioning
confidence: 99%
“…With recessive resistance and both susceptible homozygotes and heterozygotes delayed 6 d, the resistance allele frequency never changed in the 99 yr of using transgenic corn. When the homozygous susceptibles were delayed by 3Ð9 d with additive allele expression, resistance evolution did not change (Onstad et al 2001). Thus, to predict the inßuence of developmental delays, if they exist, on resistance evolution, we must know whether heterozygotes are delayed as well as whether resistance is recessive.…”
Section: Submodel For Adultsmentioning
confidence: 99%
See 1 more Smart Citation